THE ROLE OF THE ASEAN DIGITAL MASTERPLAN 2025 IN ALIGNING REGIONAL DIGITAL GOVERNANCE AND INDONESIA’S DIGITAL ECONOMIC GROWTH (2021-2024) - Fazriel Pramuditya; Diah Apriliani (PT. Hafasy Dwi Nawasena, 2026)
This study examines the role of the ASEAN Digital Masterplan 2025 (ADM 2025) in shaping Indonesia’s digital economic growth during the 2021–2024 period by focusing on its function as a regional digital governance framework. Using a qualitative approach based on document analysis and in-depth interviews, this research finds that ADM 2025 influences Indonesia’s digital economy through policy alignment mechanisms, particularly in the areas of digital infrastructure development, digital literacy enhancement, public service digitalization, and the strengthening of the digital MSME ecosystem. The findings demonstrate that ADM 2025 contributes to Indonesia’s digital economic growth by promoting regulatory coordination and institutional coherence between ASEAN-level commitments and national digital policies. Nevertheless, challenges remain, including unequal internet access, limited digital literacy among certain social groups, cybersecurity vulnerabilities, and dependence on foreign digital platforms. This study contributes to the literature by moving beyond a descriptive assessment of regional digital policy and providing an analytical understanding of how regional digital governance frameworks shape national digital economic development.